Electrode binder composition for secondary battery, and active substance layer for electrode
A copolymer composition with defined monomer properties addresses the adhesive and cycle issues of conventional binders, enhancing electrode performance in secondary batteries.
Patent Information
- Application Number
- JP2023104098
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-26
- Publication Date
- 2025-01-15
AI Technical Summary
Conventional binders for secondary batteries, such as those described in Patent Documents 1, 2, and 3, often suffer from insufficient adhesive strength and cycle characteristics, leading to impaired battery performance.
A particulate copolymer composition containing specific monomers (M1, M2, and M3) with defined properties, including a high degree of swelling, glass transition temperature, and crosslinking, which enhances adhesive strength and cycle characteristics.
The copolymer composition achieves improved adhesive strength and cycle characteristics, balancing flexibility and durability in secondary battery electrodes.
Smart Images

Figure 2025004417000001 
Figure 2025004417000002 
Figure 2025004417000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an electrode binder composition for a secondary battery and an electrode active material layer. [Background technology]
[0002] In recent years, research on non-aqueous secondary batteries, especially lithium-ion secondary batteries, has been actively conducted as an energy technology to reduce the burden on the environment. Lithium-ion secondary batteries have a large capacity per unit weight or volume compared to other battery systems, and are suitable for large-capacity and miniaturization. For example, in the automotive field, exhaust gas regulations in each country are becoming stricter every year, and with the shift to electric vehicles such as EVs, the demand for lithium-ion secondary batteries is increasing. One method for producing an electrode for a lithium ion secondary battery or the like is to apply a liquid composition (slurry) in which a binder, a thickener, etc. is added to an electrode active material onto a current collector surface and then dry the composition to form an electrode layer on the current collector. Here, styrene-butadiene copolymer latex is known as a binder that has high adhesive strength with the metal current collector and is used in aqueous blends. Binders have the function of improving the adhesion between solid active materials, between an active material and a current collector, or between an active material and a separator.
[0003] Patent Document 1 proposes composite polymer particles having a structure of two or more phases with different physical properties as a binder. Patent Document 2 proposes a resin composition for use in an electrode of an electricity storage device, which contains polymer particles having ion permeability. Patent Document 3 proposes a method of adjusting the amounts of unsaturated carboxylic acid alkyl esters, ethylenically unsaturated carboxylic acid monomers, aliphatic conjugated diene monomers, and alkenyl aromatic monomers as well as other monomers (excluding vinyl cyanide monomers) as monomers constituting the binder. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent No. 5110599 [Patent Document 2] International Publication No. 2018-021552 [Patent Document 3] Patent No. 5809636 Summary of the Invention [Problem to be solved by the invention]
[0005] Although various copolymer latexes have been proposed, there are cases where the adhesion of conventional binders is insufficient, and in such cases, the cycle characteristics during charge and discharge of the secondary battery tend to be impaired. For example, the composition described in Patent Document 1 is said to improve battery characteristics and adhesiveness by having a structure of two or more different phases, i.e., a layer that can improve adhesive strength and battery characteristics. In the case of a composition based on the description in Patent Document 1, the adhesive strength and cycle characteristics of the electrode may be insufficient. In addition, the composition described in Patent Document 2 is said to have ion permeability, thereby reducing resistance and suppressing a decrease in the retention rate of charge capacity. In Patent Document 2, the adhesion and cycle characteristics of the electrode may be insufficient. Furthermore, the composition described in Patent Document 3 is said to have excellent resistance to cracking, flexibility, and electrical conductivity of the electrode coating layer, and is also said to have excellent battery characteristics such as charge / discharge cycle characteristics. The composition described in Patent Document 3 may have insufficient adhesive strength.
[0006] An object of the present invention is to provide an electrode binder composition for a secondary battery and an electrode active material layer that can exhibit the adhesive strength and cycle characteristics of an electrode. [Means for solving the problem]
[0007] The present invention includes the following aspects. <1> A copolymer that is particulate and includes units derived from M1, M2, and M3, The M1 is a monomer having an unsaturated bond, The polymer P1 polymerized only from M1 has a swelling degree of 250% or more after immersion in an electrolyte solution or dissolves after immersion in an electrolyte solution, The glass transition temperature (Tg) of the polymer P1 is −80° C. or higher and −30° C. or lower; the content of M1 is 30% by mass or more and 90% by mass or less with respect to the total amount of units derived from all monomers, M2 is an acidic group-containing monomer having an unsaturated bond, the content of M2 is 6.0% by mass or more and 20% by mass or less with respect to the total amount of units derived from all monomers, M3 is a crosslinking monomer having two or more unsaturated bonds, the content of M3 is 0.5% by mass or more and 10% by mass or less with respect to the total amount of units derived from all monomers, The copolymer has a swelling degree of 180% or more and 400% or less after immersion in an electrolyte solution. <2> The content of M1 is 50% by mass or more based on the total amount of units derived from all monomers. <1> 2. The electrode binder composition for a secondary battery according to claim 1 . <3> The M3 includes at least one crosslinking monomer having three or more unsaturated bonds. <1> or <2> 2. The electrode binder composition for a secondary battery according to claim 1 . <4> The copolymer further comprises a unit derived from M4, The M4 is a monomer having an unsaturated bond (excluding the M2), The polymer P4 polymerized only from M4 has a swelling degree of 140% or less after immersion in an electrolyte solution, The content of M4 is 50 mass% or less based on the total amount of units derived from all monomers. <1> ~ <3> 13. The electrode binder composition for a secondary battery according to claim 12, <5> The copolymer does not contain units derived from aromatic monomers. <1> ~ <4> 13. The electrode binder composition for a secondary battery according to claim 12, <6> The glass transition temperature (Tg) of the copolymer is -25°C or more and 40°C or less. <1> ~ <5> 13. The electrode binder composition for a secondary battery according to claim 12, <7> When a film is formed using the electrode binder composition for a secondary battery, the film has an insoluble content of 90 mass % or more after immersion in an electrolyte for one day. <1> ~ <6> 13. The electrode binder composition for a secondary battery according to claim 12, <8> An active material and a particulate copolymer including units derived from M1, M2 and M3, The M1 is a monomer having an unsaturated bond, The polymer P1 polymerized only from M1 has a swelling degree of 250% or more after immersion in an electrolyte solution or dissolves after immersion in an electrolyte solution, The glass transition temperature (Tg) of the polymer P1 is −80° C. or higher and −30° C. or lower; the content of M1 is 30% by mass or more and 90% by mass or less with respect to the total amount of units derived from all monomers, M2 is an acidic group-containing monomer having an unsaturated bond, the content of M2 is 6.0% by mass or more and 20% by mass or less with respect to the total amount of units derived from all monomers, M3 is a crosslinking monomer having two or more unsaturated bonds, the content of M3 is 0.5% by mass or more and 10% by mass or less with respect to the total amount of units derived from all monomers, The copolymer has a swelling degree of 180% or more and 400% or less after immersion in an electrolyte solution. Effect of the Invention
[0008] According to the present invention, it is possible to provide an electrode binder composition for a secondary battery and an electrode active material layer that can exhibit the adhesive strength and cycle characteristics of an electrode. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Hereinafter, an embodiment of the present invention (hereinafter simply referred to as "the present embodiment") will be described in detail. The following embodiment is an example for explaining the present invention, and is not intended to limit the present invention to the following content. The present invention can be carried out with appropriate modifications within the scope of the gist of the present invention. In this specification, when a numerical value or physical property value is enclosed before and after "~", the values before and after the "~" are included. In the present specification, the upper or lower limit of one numerical range may be replaced with the upper or lower limit of another numerical range. In addition, in the present specification, the upper or lower limit of the numerical range may be replaced with a value shown in the examples. In the description of groups (atomic groups) in this specification, when there is no indication of substituted or unsubstituted, the term encompasses both unsubstituted and substituted groups. For example, the term "alkyl group" encompasses not only alkyl groups without a substituent (unsubstituted alkyl groups) but also alkyl groups with a substituent (substituted alkyl groups). In this specification, "(meth)acrylic" includes both methacryl and acrylic. In this specification, the content of each component means the total content of the corresponding component, unless otherwise specified.
[0010] <Electrode binder composition for secondary battery> The electrode binder composition for a secondary battery of the present embodiment (also simply referred to as a composition in the present embodiment) is particulate and contains a copolymer containing units derived from M1, M2, and M3, M1 is a monomer having an unsaturated bond, Polymer P1 polymerized only from M1 has a swelling degree of 250% or more after immersion in an electrolyte or dissolves after immersion in an electrolyte, The glass transition temperature (Tg) of the polymer P1 is −80° C. or higher and −30° C. or lower. the content of M1 is 30% by mass or more and 90% by mass or less based on the total amount of units derived from all monomers, M2 is an acidic group-containing monomer having an unsaturated bond, The content of M2 is 6.0% by mass or more and 20% by mass or less based on the total amount of units derived from all monomers, M3 is a cross-linking monomer having two or more unsaturated bonds, The content of M3 is 0.5% by mass or more and 10% by mass or less based on the total amount of units derived from all monomers, The copolymer has a degree of swelling of 180% or more and 400% or less after immersion in an electrolyte solution.
[0011] The electrode binder composition for a secondary battery of the present embodiment contains the above-mentioned components, and thus can exhibit the adhesive strength and cycle characteristics of the electrode.
[0012] <Copolymer> The copolymer of the present embodiment is in the form of particles and contains units derived from M1, M2 and M3.
[0013] (M1) The copolymer of this embodiment contains units derived from M1, and M1 is a monomer having an unsaturated bond.
[0014] [Swelling degree of polymer P1 after immersion in electrolyte] The polymer P1 polymerized only from M1 has a swelling degree of 250% or more after immersion in an electrolyte solution or dissolves after immersion in an electrolyte solution, which gives the copolymer flexibility and improves its ability to conform to active materials, etc., resulting in excellent cycle characteristics. From the above viewpoint, the polymer P1 polymerized only from M1 preferably has a swelling degree after immersion in an electrolyte of 250% or more, and more preferably 300% or more. As described above, the polymer P1 polymerized only from M1 can be dissolved after immersion in an electrolyte solution, and therefore there is no particular upper limit to the degree of swelling after immersion in an electrolyte solution.
[0015] [Method for measuring the swelling degree of polymer P1 after immersion in electrolyte] The degree of swelling of the polymer P1 after immersion in the electrolyte solution is measured by the following method. The composition containing polymer P1 is left to stand in an oven at 130°C for 1 hour to dry. A film of polymer P1 obtained by drying is cut out, and the mass of the film (Wa:g) is measured. The cut sample is placed in a 50mL vial together with 20g of a mixed solvent of ethylene carbonate / ethyl methyl carbonate = 1 / 2 (volume ratio), and the mixed solvent is allowed to penetrate at 60°C for 1 day. Thereafter, the film is taken out, the electrolyte is wiped off, and the mass of the film (Wb:g) is measured. The film is washed with the above mixed solvent, the mass (Wb:g) is measured, and the swelling degree of polymer P1 in the electrolyte is calculated using the following formula. Electrolyte swelling rate (%) = (Wb / Wa) x 100
[0016] [Glass transition temperature (Tg) of polymer P1] The glass transition temperature (Tg) of the polymer P1 is -80°C or higher and -30°C or lower. The copolymer particles have excellent hardness when Tg is −80° C. or higher. From the above viewpoint, Tg is preferably −70° C. or higher, and more preferably −60° C. or higher. When the Tg is −30° C. or less, the copolymer particles have excellent adhesive strength. From the above viewpoint, the Tg is preferably −40° C. or less.
[0017] [Method for measuring the glass transition temperature of polymer P1] The composition containing polymer P1 is adjusted to pH 7.0 and dried to obtain a dry product. Using a differential scanning calorimeter (e.g., SII NanoTechnology Co., Ltd.; DSC6220), the temperature is increased at a predetermined rate according to ASTM method (D3418-97), a differential scanning calorimeter curve of polymer P1 is obtained, and the glass transition temperature is determined.
[0018] The glass transition temperature and degree of swelling in an electrolyte can be adjusted to fall within the above-mentioned ranges, for example, by appropriately selecting as M1 a monomer having a low or high SP value.
[0019] The content of M1 is 30% by mass or more and 90% by mass or less based on the total amount of units derived from all monomers. When the content of M1 is 30% by mass or more, flexibility is imparted to the copolymer, and the conformability to the active material and the like can be improved, resulting in excellent cycle characteristics. From the above viewpoints, the content of M1 is preferably 35% by mass or more, more preferably 40% by mass or more, and further preferably 50% by mass or more. When the content of M1 is 90% by mass or less, the swelling ratio of the copolymer can be appropriately suppressed, and the electrode has an excellent balance between the adhesive strength and the cycle characteristics. From the above viewpoints, the content of M1 is preferably 88 mass % or less.
[0020] There are no particular limitations on M1 as long as it satisfies the above glass transition temperature and electrolyte swelling degree, and examples thereof include butyl acrylate, 4-hydroxybutyl acrylate, methoxypolyethylene glycol acrylate, and polypropylene glycol monomethacrylate. Among the above, butyl acrylate is preferable as M1 from the viewpoint of excellent adhesive strength and cycle characteristics of the electrode. As M1, one type may be used alone, or two or more types may be used in combination.
[0021] (M2) The copolymer of the present embodiment contains units derived from M2, and M2 is an acidic group-containing monomer having an unsaturated bond. The content of M2 is 6.0% by mass or more and 20% by mass or less based on the total amount of units derived from all monomers. When the content of M2 is 6.0% by mass or more, the swelling ratio of the copolymer can be appropriately suppressed, and the electrode has an excellent balance between the adhesive strength and the cycle characteristics. From the above viewpoints, the content of M2 is preferably 8.0% by mass or more, and more preferably 10.0% by mass or more. When the content of M2 is 20% by mass or less, flexibility is imparted to the copolymer, and the conformability to the active material and the like can be improved, resulting in excellent cycle characteristics. From the above viewpoints, the content of M2 is preferably 18% by mass or less, more preferably 16% by mass or less, and further preferably 14% by mass or less.
[0022] Examples of M2 include, but are not limited to, unsaturated carboxylic acids such as (meth)acrylic acid and itaconic acid, unsaturated sulfonic acids such as sodium methacryloyloxypolyoxypropylenesulfonate and vinylsulfonic acid, and unsaturated phosphoric acids such as mono(2-hydroxyethyl methacrylate)phosphate. Among the above, from the viewpoint of excellent electrode adhesive strength and cycle characteristics, M2 is preferably an unsaturated carboxylic acid, and more preferably at least one selected from the group consisting of (meth)acrylic acid and itaconic acid. As M2, one type may be used alone, or two or more types may be used in combination.
[0023] (M3) The copolymer of this embodiment contains units derived from M3, and M3 is a crosslinking monomer having two or more unsaturated bonds.
[0024] It is preferable that M3 contains at least one crosslinking monomer having three or more unsaturated bonds.
[0025] The content of M3 is 0.5% by mass or more and 10% by mass or less based on the total amount of units derived from all monomers. When the content of M3 is 0.5% by mass or more, the swelling ratio of the copolymer can be appropriately suppressed, and an excellent balance between the adhesive strength and cycle characteristics of the electrode can be achieved. From the above viewpoints, the content of M3 is preferably 0.5 mass % or more, and more preferably 1.0 mass % or more. When the content of M3 is 10% by mass or less, flexibility is imparted to the copolymer, and the conformability to the active material and the like can be improved, resulting in excellent cycle characteristics. From the above viewpoints, the content of M3 is preferably 8 mass % or less.
[0026] Examples of M3 include, but are not limited to, trimethylolpropane triacrylate, 1,9-nonanediol dimethacrylate, divinylbenzene, ethylene glycol dimethacrylate, allyl methacrylate, butadiene, propylene glycol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol tetra(meth)acrylate, diallyl fumarate, diaryl itaconate, and triallyl isocyanurate. Among the above, M3 is preferably at least one selected from the group consisting of trimethylolpropane triacrylate, 1,9-nonanediol dimethacrylate, divinylbenzene, ethylene glycol dimethacrylate, allyl methacrylate, and butadiene, from the viewpoint of excellent electrode adhesive strength and cycle characteristics. As M3, one type may be used alone, or two or more types may be used in combination.
[0027] (M4) The copolymer preferably further contains a unit derived from M4, where M4 is a monomer having an unsaturated bond (but excluding the above M2).
[0028] [Swelling degree of polymer P4 after immersion in electrolyte] Polymer P4, which is polymerized only from M4, has a swelling degree of 140% or less after immersion in an electrolyte solution, which allows the swelling rate of the copolymer to be appropriately controlled, resulting in an excellent balance between the adhesive strength of the electrode and the cycle characteristics. From the above viewpoint, the polymer P4 polymerized only from M4 preferably has a swelling degree after immersion in an electrolyte of 140% or less, and more preferably 130% or less. The polymer P4 polymerized only from M4 may have a swelling degree of 110% or more, or 120% or more, after immersion in an electrolyte solution.
[0029] [Method for measuring the swelling degree of polymer P4 after immersion in electrolyte] Except for changing the polymer P1 to the polymer P4, the swelling degree of the polymer P4 after immersion in an electrolyte solution is measured in the same manner as in the above-mentioned [Method for measuring the swelling degree of the polymer P1 after immersion in an electrolyte solution].
[0030] The content of M4 is 50 mass % or less based on the total amount of units derived from all monomers. By ensuring that the content of M4 is 50% by mass or less, flexibility can be imparted to the copolymer, improving its ability to conform to active materials and the like, and further the degree of swelling can be appropriately suppressed, resulting in excellent cycle characteristics. From the above viewpoints, the content of M4 is preferably 40% by mass or less, and more preferably 30% by mass or less. The content of M4 may be 0 mass % or more, 3 mass % or more, or 5 mass % or more.
[0031] M4 is not particularly limited, but examples thereof include 2-ethylhexyl acrylate, heptyl acrylate, octyl acrylate, 2-ethylhexyl acrylate, isodecyl acrylate, octyl methacrylate, lauryl methacrylate, octadecyl methacrylate, and tetradecyl methacrylate. Among the above, 2-ethylhexyl acrylate is preferable as M4 from the viewpoint of excellent adhesive strength and cycle characteristics of the electrode. As M4, one type may be used alone, or two or more types may be used in combination.
[0032] (Other units) The copolymer may have other units derived from monomers other than M1 to M4. Examples of other monomers besides M1 to M4 include, but are not limited to, aromatic vinyl monomers such as styrene; (meth)acrylates such as hydroxyethyl methacrylate, ethyl acrylate, and methyl methacrylate; acrylamides such as N-methylol acrylamide; and sulfonic acid group-containing monomers such as vinyl sulfonic acid. As the other monomers other than M1 to M4, one type may be used alone, or two or more types may be used in combination.
[0033] The copolymer preferably does not contain any units derived from aromatic monomers, and therefore, it is preferable that the M1 to M4 and other units do not contain aromatic rings.
[0034] [Swelling degree of copolymer after immersion in electrolyte] The copolymer has a degree of swelling of 180% or more and 400% or less after immersion in an electrolyte solution. When the copolymer has a swelling degree of 180% or more, flexibility is imparted to the copolymer, which can improve the conformity to the active material and the like, resulting in excellent cycle characteristics. From the above viewpoints, the copolymer preferably has a swelling degree after immersion in an electrolyte of 185% or more, and more preferably 190% or more. By controlling the swelling degree of the copolymer to 400% or less, the swelling rate of the copolymer can be appropriately controlled, and an excellent balance between the adhesive strength of the electrode and the cycle characteristics can be achieved. From the above viewpoints, the copolymer preferably has a swelling degree after immersion in an electrolyte of 385% or less, and more preferably 365% or less.
[0035] [Method for measuring the swelling degree of copolymer after immersion in electrolyte solution] Except for changing polymer P1 to a copolymer, the swelling degree of the copolymer after immersion in an electrolyte solution is measured in the same manner as described in the above-mentioned [Method for measuring swelling degree of polymer P1 after immersion in an electrolyte solution].
[0036] [Glass transition temperature (Tg) of copolymer] The glass transition temperature (Tg) of the copolymer is preferably from -25°C to 40°C. By having a Tg of -25°C or higher, the adhesive strength of the copolymer to the electrode at room temperature can be improved, and the cycle characteristics are well-balanced. From the above viewpoints, the Tg is more preferably −23° C. or higher, and further preferably −20° C. or higher. By making the Tg equal to or lower than 40° C., flexibility can be imparted to the copolymer, which can improve the conformability to active materials and the like, resulting in excellent cycle characteristics. From the above viewpoints, the Tg is more preferably 35° C. or lower, and further preferably 30° C. or lower.
[0037] [Method for measuring glass transition temperature of copolymer] The glass transition temperature of the copolymer is measured by the same method as that described in the above "Method for measuring the glass transition temperature of polymer P1" except that polymer P1 is changed to a copolymer.
[0038] [Insoluble portion of copolymer after immersion in electrolyte] When a membrane is formed using the secondary battery electrode binder composition, the membrane preferably has an insoluble content of 90 mass % or more after immersion in an electrolyte for one day. When the insoluble content is 90% by mass or more, the copolymer has excellent resistance to an electrolyte and excellent cycle characteristics. From the above viewpoints, the insoluble content is preferably 97% by mass or more. The insoluble content may be 100% by mass or less.
[0039] [Method of adjusting electrolyte swelling degree] The method for adjusting the electrolyte swelling degree of the copolymer or various polymers in this embodiment to the above-mentioned numerical range is not particularly limited. For example, a method focusing on the solubility parameter (hereinafter also referred to as "SP value") of a monomer component can be mentioned. Specifically, a method of using a monomer component with a high SP value and a monomer component with a low SP value as a standard based on the SP value of a general electrolyte, a method of increasing or decreasing the content ratio of each monomer component while considering the SP value of each monomer component, and the like can be mentioned. In this specification, the SP value means a solubility parameter δ calculated by the following formula (A) using the cohesive energy density (E) and molar volume (V) of various atomic groups described in "RF Edors: Polym. Eng. Sci., 14[2], 147-154(1974)". δ=ΣE / ΣV (A) (In formula (A), E and V respectively represent the E of various atomic groups and the molar volume V according to Fedors.)
[0040] The SP value of a typical electrolyte solution is, for example, about 11, but is not limited to the following. According to this example, a monomer component having an SP value of more than 11 can be treated as a high SP value component, and a monomer component having an SP value of less than 11 can be treated as a low SP value component.
[0041] The electrode binder composition for a secondary battery of the present embodiment preferably further contains an isothiazolinone compound. The content of the isothiazolinone compound is preferably 0.0001 to 1.0 parts by mass per 100 parts by mass of the copolymer. When the content is within the above range, hysteretic viscosity behavior against shear force can be suppressed, and more stable coatability tends to be achieved.
[0042] The isothiazoline compound is not particularly limited, and various known compounds can be used. For example, 2-methyl-4-isothiazolin-3-one, 5-chloro-2-methyl-4-isothiazolin-3-one, 1,2-benzoisothiazolin-3-one, 2-n-octyl-4-isothiazolin-3-one, 4,5-dichloro-2-n-octyl-4-isothiazolin-3-one, 2-ethyl-4-isothiazolin-3-one, 4,5-dichloro-2-cyclohexyl-4-isothiazolin-3-one, 5-chloro-2-ethyl-4-isothiazolin-3-one, 5-chloro-2-t-octyl-4-isothiazolin-3-one, 4-chloro-2-n-octyl-4-isothiazolin-3-one, Examples of the isothiocyanate include azolin-3-one, 5-chloro-2-n-octyl-4-isothiazolin-3-one, Nn-butyl-1,2-benzisothiazolin-3-one, N-butylbenzisothiazolin-3-one, N-methylbenzisothiazolin-3-one, N-ethylbenzisothiazolin-3-one, N-propylbenzisothiazolin-3-one, N-isobutylbenzisothiazolin-3-one, N-pentylbenzisothiazolin-3-one, N-isopentylbenzisothiazolin-3-one, N-hexylbenzisothiazolin-3-one, N-allylbenzisothiazolin-3-one, and N-(2-butenyl)benzisothiazolin-3-one. Among the above, 2-methyl-4-isothiazolin-3-one is preferred.
[0043] The electrode binder composition for a secondary battery of the present embodiment may contain an antifoaming agent as an optional component. Examples of the defoaming agent include various defoaming agents based on mineral oil, silicone, acrylic, and polyether. When a defoaming agent is contained, the defoaming property tends to be more excellent. In this case, the types and blending ratios of the optional components are not particularly limited.
[0044] The electrode binder composition for a secondary battery of the present embodiment can contain an emulsifier as an optional component. The emulsifier is not particularly limited, but examples thereof include anionic surfactants, nonionic surfactants, amphoteric surfactants, reactive surfactants, etc. The emulsifiers can be used alone or in combination of two or more kinds.
[0045] The anionic surfactant is not particularly limited, but examples thereof include sulfate esters of higher alcohols, alkylbenzene sulfonates, aliphatic sulfonates, and sulfate esters of polyethylene glycol alkyl ethers.
[0046] The nonionic surfactant is not particularly limited, but examples thereof include alkyl ester type, alkyl ether type, and alkyl phenyl ether type of polyethylene glycol.
[0047] The amphoteric surfactant is not particularly limited, but examples thereof include betaines such as lauryl betaine and stearyl betaine, and amino acid types such as lauryl-β-alanine, stearyl-β-alanine, and lauryl di(aminoethyl)glycine.
[0048] The reactive surfactant is not particularly limited, but examples thereof include polyoxyethylene alkylpropenylphenyl ether, α-[1-[(allyloxy)methyl]-2-(nonylphenoxy)ethyl]-ω-hydroxypolyoxyethylene, and the like.
[0049] The electrode binder composition for a secondary battery of the present embodiment can contain a polymerization initiator as an optional component. The polymerization initiator is not particularly limited, but examples thereof include water-soluble polymerization initiators such as sodium persulfate, potassium persulfate, and ammonium persulfate, oil-soluble polymerization initiators such as benzoyl peroxide and lauryl peroxide, and redox-based polymerization initiators in combination with a reducing agent, etc. The polymerization initiators can be used alone or in combination of two or more kinds.
[0050] (Application) The composition of the present embodiment is used as an electrode binder for secondary batteries. In addition to the copolymer particles of the present embodiment, various known optional components may be included depending on the application. The application of the composition of the present embodiment is not particularly limited as long as it is used as one material of an electrode binder for a secondary battery. For example, the composition of the present embodiment can be used as a negative electrode material, a positive electrode material, a separator material, etc.
[0051] <<Method for producing electrode binder composition for secondary battery>> The method for producing the composition of the present embodiment is not particularly limited, but it can be preferably produced by the following production method (hereinafter also referred to as the "production method of the present embodiment"). That is, in order to obtain a composition containing polymer particles, a method of carrying out emulsion polymerization using the above-mentioned raw material monomers, etc. is preferred. Appropriate seed particles can be used during polymerization, and the seed particles can also be obtained by normal emulsion polymerization. For the emulsion polymerization, a known method can be adopted, and the production can be carried out in an aqueous medium by appropriately using a polymerization initiator, a molecular weight regulator, a chelating agent, a pH regulator, an emulsifier, etc.
[0052] In the production method of this embodiment, the conditions such as stirring speed, polymerization temperature, reaction (polymerization) time, etc. are not particularly limited as long as the composition of this embodiment can be obtained. Typically, the stirring speed can be usually 50 rpm or more and 500 rpm or less, the polymerization temperature can be usually 50 ° C. or more and 100 ° C. or less, and the reaction time can be usually 3 hours or more and 72 hours or less.
[0053] In the method of the present embodiment, after the polymer particles are obtained as described above, the polymer particles are dispersed in a dispersion medium as necessary, and an optional component is added to obtain the composition of the present embodiment. Water can be used as the dispersion medium, and an organic solvent suitable for the active material can also be used as necessary.
[0054] <<Active material layer for electrode>> The electrode active material layer of the present embodiment includes an active material and a particulate copolymer including units derived from M1, M2, and M3, M1 is a monomer having an unsaturated bond, Polymer P1 polymerized only from M1 has a swelling degree of 250% or more after immersion in an electrolyte or dissolves after immersion in an electrolyte, The glass transition temperature (Tg) of the polymer P1 is −80° C. or higher and −30° C. or lower. the content of M1 is 30% by mass or more and 90% by mass or less based on the total amount of units derived from all monomers, M2 is an acidic group-containing monomer having an unsaturated bond, The content of M2 is 6.0% by mass or more and 20% by mass or less based on the total amount of units derived from all monomers, M3 is a cross-linking monomer having two or more unsaturated bonds, The content of M3 is 0.5% by mass or more and 10% by mass or less based on the total amount of units derived from all monomers, The copolymer has a degree of swelling of 180% or more and 400% or less after immersion in an electrolyte solution.
[0055] The electrode active material layer of this embodiment can be obtained by the electrode binder composition for secondary batteries of this embodiment described above. Therefore, the specific aspects and preferred aspects of the copolymer, M1, M2, M3, M4, and other monomers in the electrode binder composition for secondary batteries of this embodiment can also be applied to the electrode active material layer of this embodiment.
[0056] <Active material> The electrode active material layer of the present embodiment contains an active material. The active material can include a positive electrode active material and a negative electrode active material.
[0057] The positive electrode active material is not particularly limited, but examples thereof include lithium-containing composite oxides, transition metal oxides, transition metal fluorides, and transition metal sulfides.
[0058] The lithium-containing composite oxide is not particularly limited, but examples thereof include LiCoO2, LiMnO2, LiNiO2, LiMn2O4, LiXCoYSnZO2, LiFePO4, and LiXCoYSnZO2. The transition metal oxide is not particularly limited, but examples thereof include MnO2, MoO3, V2O5, and V6O 13 , Fe2O3, Fe3O4, etc. The transition metal fluoride is not particularly limited, but examples thereof include CuF2, NiF2, and the like. The transition metal sulfide is not particularly limited, but examples thereof include TiS2, TiS3, MoS3, and FeS2.
[0059] The negative electrode active material is not particularly limited, but examples thereof include materials capable of absorbing and releasing metal ions, specifically, carbon-based active materials, silicon-based active materials, and the like.
[0060] Examples of carbon-based active materials include graphite, carbon fiber, coke, hard carbon, mesocarbon microbeads (MCMB), baked furfuryl alcohol resin (PFA), and conductive polymers (poly-p-phenylene, etc.). Silicon-based active materials include silicon, SiO x (0.01≦x<2), alloys of silicon and transition metals, etc. Among the above, the active material preferably includes a negative electrode active material, more preferably includes a carbon-based active material, and further preferably includes graphite.
[0061] The electrode active material layer of this embodiment may be a positive electrode active material layer or a negative electrode active material layer. EXAMPLES
[0062] The present embodiment will be described more specifically below with reference to examples, but the present embodiment is not limited to these examples in any way.
[0063] The details of the components in this example are as follows: (M1) BA Butyl acrylate (Tg of polymer P1: -52°C, swelling degree: soluble) (M2) MAA Methacrylic acid AA Acrylic Acid IA Itaconic Acid Sodium methacryloyloxypolyoxypropylene sulfonate (M3) A-TMPT Trimethylolpropane Triacrylate (manufactured by Shin-Nakamura Chemical Co., Ltd.) 1,9-ND 1,9-nonanediol dimethacrylate DVB Divinylbenzene EDGMA Ethylene glycol dimethacrylate Allyl methacrylate butadiene (M4) 2-EHA 2-Ethylhexyl acrylate (Tg of polymer P4: -70°C, swelling degree: 130%) (others) St Styrene HEMA Hydroxyethyl Methacrylate EA Ethyl acrylate MMA Methyl methacrylate N-Methylolacrylamide
[0064] [Example 1] 0.9 parts by mass of polyoxyethylene polycyclic phenyl ether sulfate ammonium salt (manufactured by Nippon Nyukazai Co., Ltd., "New Coal 707-SF") and 400 parts by mass of ion-exchanged water were added to a reactor, and the temperature was raised to 70°C while stirring and maintained. 1.5 parts by mass of sodium persulfate (hereinafter also referred to as "NPS") was added to the reactor. A monomer solution of 231 parts by mass of butyl acrylate, 51 parts by mass of methacrylic acid, 15 parts by mass of 2-ethylhexyl acrylate, and 3 parts by mass of trimethylolpropane triacrylate, 3.0 parts by mass of New Coal 707-SF, and 300 parts by mass of ion-exchanged water were added to the reactor. The resulting mixture was emulsified with a homogenizer, and the resulting emulsion was added dropwise. The temperature was kept at 70°C, and the dropwise addition was completed in 2.5 hours, after which polymerization was continued for 2 hours. The temperature was then raised from 70°C to 80°C, and maintained for 1 hour to complete the polymerization, obtaining copolymer particles. The contents of the units derived from each monomer in the obtained copolymer particles are shown in Table 1.
[0065] To 100 parts by mass of the obtained copolymer particles, 0.0005 parts by mass of methylisothiazoline was added as an additive, and then the mixture was filtered using a 200 μm mesh. The polymerization rate was 99%. The obtained polymer particles were neutralized by adding 6.4 parts by mass of a 10% aqueous sodium hydroxide solution to obtain a composition. The obtained composition had a pH of 7.7 and a solid content of 29%. The polymerization rate was calculated by adding the solid content rate to the ratio of the amount of residue to the amount of all charged components.
[0066] <Preparation of coating solution for secondary battery negative electrode> To the obtained composition (2.0 parts by weight of solid content), 1.0 parts by weight of carboxymethyl cellulose as a thickener component and 100 parts by weight of natural graphite as a negative electrode active material were further added, and ion-exchanged water was added thereto, and the mixture was stirred with a mechanical stirrer to prepare a total solid content of 60%. This was used as a premix, and was then dispersed for 30 seconds at a peripheral speed of 20 m / s using a thin-film rotating high-speed mixer (TK Filmmix FM56-L type (product name) manufactured by PRIMIX Corporation) to prepare a coating solution for secondary battery negative electrodes.
[0067] [Examples 2 to 18 and Comparative Examples 1 to 9] In each example, the types and / or amounts of the monomers and additives were changed so that the content of units derived from each monomer in the resulting copolymer particles was as shown in Tables 1 to 3. Except for this, the compositions of Examples 2 to 18 and Comparative Examples 1 to 9 were prepared in the same manner as in Example 1, and coating fluids for secondary battery negative electrodes were produced. The composition and the secondary battery negative electrode obtained as described above were used for various evaluations. The results are shown in Tables 1 to 3.
[0068] <Preparation of negative electrode for peel test> The coating solution was applied to one side of a copper foil using a die coater so that the thickness after drying was 100 μm, and then dried at 60° C. for 60 minutes. After drying at 120° C. for 3 minutes, the foil was compression molded using a roll press machine to obtain a negative electrode active material with a bulk density of 1.60 g / cm. 3 It was made to be like this. <Preparation of secondary battery negative electrode> The coating solution was applied to one side of a copper foil using a die coater so that the thickness after drying was 100 μm, and then dried at 60° C. for 60 minutes. After drying at 120° C. for 3 minutes, the negative electrode active material was compression molded using a roll press machine to obtain a bulk density of 1.49 g / cm. 3 It was made to be like this.
[0069] [Evaluation method] (glass transition temperature) The composition containing the copolymer particles was adjusted to pH 7.0 and dried at 130°C for 30 minutes to obtain a dried product. Using a differential scanning calorimeter (manufactured by SII Nano Technology Co., Ltd.; DSC6220), the temperature was raised from -50°C to +200°C at a rate of 20°C / min according to the ASTM method (D3418-97), a differential scanning calorimeter curve of the copolymer particles was obtained, and the glass transition temperature was determined using the attached software. Whether the glass transition temperature was one or two or more was determined by finding the peaks by judging using the software.
[0070] (Electrolyte swelling degree) The composition containing the copolymer particles, polymer P1 or polymer P4 was left to stand in an oven at 130°C for 1 hour to dry. The film of the polymer particles obtained by drying was cut out, and the mass of the film (Wa:g) was measured. The cut sample was placed in a 50mL vial together with 20g of a mixed solvent of ethylene carbonate / ethyl methyl carbonate = 1 / 2 (volume ratio), and the mixed solvent was allowed to penetrate at 60°C for 1 day, after which the film was taken out, the electrolyte was wiped off, and the mass of the film (Wb:g) was measured. The film was washed with the mixed solvent, the mass (Wb:g) was measured, and the swelling degree of the copolymer with respect to the electrolyte was calculated from the following formula. Electrolyte swelling rate (%) = (Wb / Wa) x 100
[0071] (Electrolyte insoluble matter) The composition containing the copolymer particles was left to stand in an oven at 130°C for 1 hour and dried. The film of the polymer particles obtained by drying was cut out, and the mass of the film (Wa:g) was measured. The cut sample was placed in a 50mL vial together with 20g of a mixed solvent of ethylene carbonate / ethyl methyl carbonate = 1 / 2 (volume ratio), and the mixed solvent was allowed to penetrate at 60°C for 1 day, after which the film was taken out and washed with the mixed solvent. The sample was then left to stand in an oven at 150°C for 1 hour, after which the mass was measured (Wc:g), and the insoluble content of the copolymer in the electrolyte was calculated using the following formula and evaluated according to the following criteria. Electrolyte insoluble content (%)=(Wc / Wa)×100 3: Over 97%. 2: 90% or more but less than 97%. 1: Less than 90%.
[0072] (Peel strength) A test piece measuring 2 cm wide x 12 cm long was cut out from the obtained negative electrode of the secondary battery, and the surface of the current collector side of this test piece was attached to an aluminum plate with double-sided tape. In accordance with JIS Z 1522, a tape measuring 18 mm wide (trade name "Cellotape (registered trademark)" (manufactured by Nichiban Co., Ltd.)) was attached to the electrode layer side of the test piece, and the strength when the tape was peeled off in a 180° direction at a speed of 100 mm / min was measured six times, and the average value (N / 18 mm) was calculated as the peel strength (before immersion in electrolyte). The larger these values are, the higher the adhesive strength between the current collector and the electrode layer is, and it can be evaluated that it is difficult to peel the electrode layer from the current collector. Specifically, the peel strength was evaluated based on the following criteria. 5:12N / m or more. 4: 11N / m or more and less than 12N / m. 3: 10N / m or more and less than 11N / m. 2: 9N / m or more and less than 10N / m. The ratio was less than 1:9N / m.
[0073] (Cycle characteristics) The secondary battery produced by the following method using the secondary battery negative electrode was charged at a constant current of 4.2 V at 60° C. using a constant current / constant voltage charging method of 2 C. Thereafter, a charge / discharge cycle was performed in which the battery was charged at a constant voltage and then discharged at a constant current of 1 C to 3.0 V. The cycle test was performed up to 200 cycles, and the ratio of the discharge capacity at the 200th cycle to the initial discharge capacity was taken as the capacity retention rate and was judged according to the following criteria. The larger this value, the smaller the capacity loss due to repeated charging and discharging. 5: The capacity retention rate was 92.0% or more. 4: The capacity retention rate was 91.5% or more and less than 92.0%. 3: The capacity retention rate was 91.0% or more and less than 91.5%. 2: The capacity retention rate was 90.0% or more and less than 91.0%. 1: The capacity retention rate was less than 90.0%.
[0074] [Table 1]
[0075] [Table 2]
[0076] [Table 3]
[0077] As shown in Tables 1 to 3, the polymer P1 is particulate and contains a copolymer containing units derived from M1, M2, and M3, M1 being a monomer having an unsaturated bond, and polymer P1 polymerized only from M1 has a swelling degree of 250% or more after immersion in an electrolyte solution or dissolves after immersion in an electrolyte solution, the glass transition temperature (Tg) of polymer P1 is -80°C or more and -30°C or less, the content of M1 is 30% by mass or more and 90% by mass or less with respect to the total amount of units derived from all monomers, and M2 is an unsaturated bond. The content of M2 is 6.0 mass% or more and 20 mass% or less with respect to the total amount of units derived from all of the monomers, M3 is a crosslinking monomer having two or more unsaturated bonds, the content of M3 is 0.5 mass% or more and 10 mass% or less with respect to the total amount of units derived from all of the monomers, and the copolymer has a swelling degree of 180% or more and 400% or less after immersion in an electrolyte solution. Examples using this electrode binder composition for secondary batteries were excellent in adhesive strength and cycle characteristics. On the other hand, Comparative Examples 1, 3, 4 and 7, in which the degree of swelling of the copolymer after immersion in the electrolyte solution was less than 180%, were inferior in adhesive strength and cycle characteristics as compared with the Examples. Comparative Examples 2, 6 and 8, in which the degree of swelling of the copolymer after immersion in the electrolyte exceeded 400%, were inferior in adhesive strength and cycle characteristics to the Examples. Comparative Example 5, in which the content of M3 exceeded 10 mass %, was inferior in adhesive strength and cycle characteristics to the Examples. Comparative Example 9, in which the content of M2 exceeded 20 mass %, was inferior in adhesive strength and cycle characteristics to the Examples.
Claims
1. The copolymer is particulate and includes units derived from M1, M2, and M3, M1 is a monomer having an unsaturated bond, The polymer P1 polymerized only from M1 has a swelling degree of 250% or more after immersion in an electrolyte solution or dissolves after immersion in an electrolyte solution; The glass transition temperature (Tg) of the polymer P1 is −80° C. or higher and −30° C. or lower; the content of M1 is 30% by mass or more and 90% by mass or less with respect to the total amount of units derived from all monomers, M2 is an acidic group-containing monomer having an unsaturated bond, the content of M2 is 6.0% by mass or more and 20% by mass or less with respect to the total amount of units derived from all monomers, M3 is a crosslinking monomer having two or more unsaturated bonds, The content of M3 is 0.5% by mass or more and 10% by mass or less with respect to the total amount of units derived from all monomers, The copolymer has a swelling degree of 180% or more and 400% or less after immersion in an electrolyte solution.
2. The electrode binder composition for a secondary battery according to claim 1 , wherein the content of M1 is 50 mass % or more based on the total amount of units derived from all monomers.
3. The electrode binder composition for a secondary battery according to claim 1 , wherein M3 comprises at least one crosslinking monomer having three or more unsaturated bonds.
4. The copolymer further comprises a unit derived from M4, The M4 is a monomer having an unsaturated bond (excluding the M2), The polymer P4 polymerized only from M4 has a swelling degree of 140% or less after immersion in an electrolyte solution, The electrode binder composition for secondary batteries according to claim 1 , wherein the content of M4 is 50 mass % or less based on the total amount of units derived from all monomers.
5. The electrode binder composition for secondary batteries according to claim 1 , wherein the copolymer does not contain any unit derived from an aromatic monomer.
6. 2. The electrode binder composition for a secondary battery according to claim 1, wherein the glass transition temperature (Tg) of the copolymer is −25° C. or more and 40° C. or less.
7. 2. The electrode binder composition for a secondary battery according to claim 1, wherein when a film is formed using the electrode binder composition for a secondary battery, the film has an insoluble content of 90 mass% or more after being immersed in an electrolyte for one day.
8. An active material and a particulate copolymer including units derived from M1, M2 and M3, M1 is a monomer having an unsaturated bond, The polymer P1 polymerized only from M1 has a swelling degree of 250% or more after immersion in an electrolyte solution or dissolves after immersion in an electrolyte solution; The glass transition temperature (Tg) of the polymer P1 is −80° C. or higher and −30° C. or lower; the content of M1 is 30% by mass or more and 90% by mass or less with respect to the total amount of units derived from all monomers, M2 is an acidic group-containing monomer having an unsaturated bond, the content of M2 is 6.0% by mass or more and 20% by mass or less with respect to the total amount of units derived from all monomers, M3 is a crosslinking monomer having two or more unsaturated bonds, The content of M3 is 0.5% by mass or more and 10% by mass or less with respect to the total amount of units derived from all monomers, The copolymer has a swelling degree of 180% or more and 400% or less after immersion in an electrolyte solution.
Citation Information
Patent Citations
Funenokyumeisochi
JP1976010599A
Fishing line knotter of electromotive fishing hook
JP1983009636A
Resin composition for power storage device electrode
WO2018021552A1
Cited By
Battery cell and preparation method therefor, polymer, and electric device
WO2026200188A1